Influence of underground cable insulation parameters on transient overvoltages - Fessol F.N.; Mohd Ariffin A.; Illias H.A. (2023)
It is a well-accepted fact that the protection of power system equipment is very crucial in order to ensure sustainability of electrical energy delivery. Each equipment is subjected to different types of surges and these surges can be of different amplitudes and frequencies. Depending on the severity of the transient surges, the equipment might experience very severe damages and also can cause further disruption to the overall electrical network. Failure of underground cables has always been a major concern for the electrical power distribution industries. Fault location and repair of faulty cables are expensive and time-consuming. Overvoltage phenomena such as line switching, load rejection and fault produce high frequency transients that could affect the performance of an underground cable and also the network that it is connected to. Therefore it is important to identify the factors that dictate the behaviour of a transient signal travelling along the cable. This paper will look into the simulation studies on transient behaviour when the characteristics representing the insulation of underground cables are varied. By identifying the causes that contribute to the change of cable characteristics, the effects they have on the simulated transient can be examined thoroughly. 2013 IEEE.